Forensic Determination of Wet Drowning in a River Utilizing Pennales Diatom Analysis: A Forensic Autopsy Report - Nuriman, R. Ananda; Bumi Agung, I Gusti Lanang; Setiawardani, Alvina; Yudianto, Ahmad; Sumino, Renny; Ramadhani, Prasillia (International Journal of Medical Toxicology and Forensic Medicine, 2026)
Background: Drowning remains a significant cause of unintentional mortality, requiring comprehensive forensic investigation to determine the mechanism and circumstances of death. Case Presentation: This case report is about a 30-year-old person whose name is not known and who was found in a freshwater river. After that, they were examined on the outside, inside and in other ways. The external findings included fine, frothy fluid coming from the airways, livor mortis that made the skin look pale, rigor mortis of the upper extremities, signs of hypoxia, and maceration of the hands. An internal examination found the Nile sign, no structural problems with the major organs, and stomach contents that were consistent with recent eating. Ancillary tests showed a positive diatom test with Pennales diatoms found in over 10 fields, which supports the idea of freshwater drowning. Conclusion: However, the lung fluid study had a chance of false positives because the body had been preserved for a long time. This case underscores the persistent necessity for comprehensive forensic evaluation encompassing diatom analysis, organ examination and contextual interpretation to ascertain drowning as the cause of death.